Atividade Inseticida de extratos obtidos a partir do resíduo líquido de Agave sisalana Perr. no controle da praga Spodoptera frugiperda (J.E. SMITH, 1797) (Lepidoptera: Noctuidae) em Zea mays - Souza, Marcela Fonseca (2009)
The use of chemical for pests control is widely applied in the cultive of plants, which destroy and dismount the stability ecologic of the natural system. Because they are least aggressive and possess more then one active principle in the beginning the natural pesticides of origin vegetable can minimize unwanted consequences. This work was carried out to determine the insecticidal activity of extracts obtained from organic waste liquid of Agave sisalana on Spodoptera frugiperda. Firstly, for the utilization in bioactivity tests, experiments aiming the determination of the most appropriate extract concentrations were conduced, being used hydroethanolic extracts in three concentrations (1,25%, 2,5% e 5%) for tests of ingestion and contact. In all bioassays were utilization two control treatments, one water and the other chemical insecticide (Decis®). biological tests was performed for evaluation of insecticidal activity of organic extracts of A. sisalana on S. frugiperda (hydroethanolic, Butanolic, Ethyl acetate e aqueous) hydroethanolic extracts and butanólico was considered the most effective on the pest. As the hydroethanolic extract was obtained in greater quantity, it was tested in field the 5g, 8g e 10g was also observed in the phytotoxicity of extracts from maize plants. According to the resukts it was possible to conclude than the mayze leaves immersed with Butanolic and hydroethanolic extracts (10g/100mL) of Agave sisalana, ingested by larvae of S. frugiperda, a significant mortality rate (90 % e 88%, after 72 h). The maize plants sprayed with EtOH 8g/100mL e EtOH 10g/100mL. these were extracts of Agave sisalana that had more reduction in damage caused by Spodoptera frugiperda, however the last obtained a significant reduction of damage after the third application. The extract of EtOH 10g/100mL was the most effective to contain the damage caused by Spodoptera frugiperda. As to phytotoxicity was not observed significant increase in phytotoxicity with increasing number of applications. Increasing the concentration of the hydroethanolic extracts significantly increases phytotoxicity. The hydroethanolic extracts 2,5 e 5g/100 mL are indicated for possible use in controlling pests in corn by presenting low phytotoxicity.